Аудит інформаційної безпеки в інфраструктурі хмарних обчислень - Коханевич, Є. Г. (ХНУРЕ, 2019)
In this work the features of information security of cloud infrastructure are considered. Also we created a test environment using the OpenStack program, and simulates the work of cloud computing services to identify the major threats. Then, we identified the main metrics with which you can identify the incident of information security in the cloud. In the end, a neural network was created that was capable of responding to information security incidents in accordance with data obtained from metrics.